PENGENDALIAN PERSEDIAAN BAHAN BAKU OBAT DENGAN MENGGUNAKAN METODE EOQ PROBABILISTIK BERDASARKAN PERAMALAN EXPONENTIAL SMOOTHING PADA PT. XYZ - Fila Dristiana; Tedjo Sukmono (Universitas Ahmad Dahlan Indonesia, 2015)
PT. XYZ is one of the manufactures of parmacheutical. Problems which often appeared are surplus and shortage material. Inventory material control not optimum because order only esimate. With exponential smoothing method can be devise of demand next period and EOQ Probabilistic for to know economic order quantity, total safety stock and reorder point so can minimization inventory cost. Purpose of research are to know exponential smoothing method what representatif for manufacture and give recomendation of this research. Results of research are exponential smoothing method representatif for manufacture and EOQ probabilistic method for Antalgin, Paracetamol and Piroxicam material are economic order quantity in the amount of 313 kg, 928 kg and 33 kg, safety stock 160 kg, 403 kg and 2kg and reorder point 325 kg, 1080 kg dan 14 kg. So total inventory cost of Antalgin, Paracetamol and Piroxicam material in the amount of Rp.3.847.146, Rp.5.025.081 and Rp.1.932.255. Keyword : Inventory, Exponential Smoothing, EOQ Probabilistic